PLACE IN THE 20TH CENTURY WERE IMPACT ON LIFESTYLE - Iskandarov Sherzod Abduganievich (Web of Journals Publishing, 2025)
By the 1920s, the country's life and the livelihood of the local population were in dire straits. The severe consequences of World War I, the brutal and brutal policies of the Bolshevik rulers against the local population during the establishment of the new Soviet system were evident at every step.